2014
DOI: 10.1289/ehp.1306499
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Blood Trihalomethane Concentrations in NHANES 1999–2006

Abstract: Background: Trihalomethanes (THMs) are water disinfection by-products that have been associated with bladder cancer and adverse birth outcomes. Four THMs (bromoform, chloroform, bromodichloromethane, dibromochloromethane) were measured in blood and tap water of U.S. adults in the National Health and Nutrition Examination Survey (NHANES) 1999–2006. THMs are metabolized to potentially toxic/mutagenic intermediates by cytochrome p450 (CYP) 2D6 and CYP2E1 enzymes.Objectives: We conducted exploratory analyses of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 40 publications
4
28
1
Order By: Relevance
“… Silva et al (2013) also found that blood THM concentrations dropped rapidly during the first 30 min after showering among 100 study participants following a controlled showering exposure. Consistent with two previous reports, TCM was the main component of blood TTHMs in our study population (> 70%) ( Miles et al 2002 ; Riederer et al 2014 ). The median concentrations of blood THM were higher than reported for a representative sample of U.S. adults (National Health and Nutrition Examination Survey participants in 1999–2006) ( Riederer et al 2014 ) and a group of 150 U.S. women ( Rivera-Núñez et al 2012 ), but were similar to levels reported for 401 men from Wuhan, China ( Zeng et al 2013 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… Silva et al (2013) also found that blood THM concentrations dropped rapidly during the first 30 min after showering among 100 study participants following a controlled showering exposure. Consistent with two previous reports, TCM was the main component of blood TTHMs in our study population (> 70%) ( Miles et al 2002 ; Riederer et al 2014 ). The median concentrations of blood THM were higher than reported for a representative sample of U.S. adults (National Health and Nutrition Examination Survey participants in 1999–2006) ( Riederer et al 2014 ) and a group of 150 U.S. women ( Rivera-Núñez et al 2012 ), but were similar to levels reported for 401 men from Wuhan, China ( Zeng et al 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although it has been suggested that blood concentrations at a single point in time may reflect steady-state levels ( Blount et al 2011 ), high-exposure events such as showering, bathing, and swimming can have a substantial effect on blood concentrations ( Nuckols et al 2005 ; Silva et al 2013 ). Changes in routine water-use activities in late pregnancy, and dietary changes (e.g., fasting) before delivery, also may cause blood THM concentrations to fluctuate, both within and between days ( Ashley et al 2005 ; Riederer et al 2014 ). Thus, future studies should collect multiple blood samples to provide a more accurate measure of steady-state levels, and use longer-lived exposure biomarkers (e.g., protein or DNA adducts) to avoid this limitation ( Blount et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, TTHM exposures in this sample were relatively low; only ~5% of the study population had household tap water TTHM levels that exceeded the MCL. These levels are consistent with previously published values among NHANES participants during the same time frame (Riederer et al, 2014). …”
Section: Discussionsupporting
confidence: 93%
“…Levels in exhaled air are useful in evaluating short-term exposure [41], and levels in the blood have been used in evaluations at the population level [42,43]. However, these biomarkers are of limited use for evaluating risks associated with cancer, reproductive outcomes, and other health effects that require longer exposure periods.…”
Section: Exposure Assessment In Human Epidemiological Studiesmentioning
confidence: 99%